Clinicopathological and Immunomicroenvironment Characteristics of Epstein–Barr Virus-Associated Gastric Cancer in a Chinese Population - Jia, Xiaoxia; Guo, Ting; Li, Zhemin; Zhang, Meng; Feng, Yi; Dong, Bin; Li, Zhongwu; Hu, Ying; Li, Ziyu; Xing, Xiaofang; Jia, Shuqin; Ji, Jiafu (Frontiers in Oncology, 2021)
Background: Epstein-Barr virus-associated gastric cancer（EBVaGC）has a unique tumor immune microenvironment. We performed a comprehensive analysis of the tumor-infiltrating immune cells in a cohort of EBVaGC in a Chinese population. Methods: Epstein-Barr encoding region (EBER) in situ hybridization were performed in 1328 consecutive cases of surgically resected GC. Densities of immune cells, including T cells, B cells, natural killer cells, and macrophages, from the patients were calculated after immunohistochemical staining with CD3, CD20, CD57, and CD68 antibodies in tissue microarrays, respectively. Results: EBVaGC patients accounted for 4.1% (55 of 1328) cases in the overall population. The average age of patients with EBVaGC was lower than that of non-EBVaGC patients.Histologically, EBVaGC patients exhibited poorly differentiated adenocarcinoma (P=0.004) and lower frequency of vascular invasion (P=0.034). The density of CD3+ T lymphocytes （CD3, 23.84 ± 14.49 vs. 12.76 ± 8.93, P<0.001）and CD68+ macrophages （CD68, 9.73 ± 5.25 vs. 5.44 ± 4.18, P<0.001）were significantly higher in EBVaGC patients. CD3+ T cell density predicted better 5-year overall survival of EBVaGC patients (P=0.022). Conclusions: EBVaGC patients were younger with low-differentiated adenocarcinoma, and less vascular invasion. Increased infiltration of multiple immune cells affectedthe prognosis of patients, especially EBVaGC patients with more CD3+ T lymphocytes, who survived longer.